An Analysis of Reports by The Illustrated London News (ILN) and The Graphic against Social Activities in Malaya in the 19th Century - Azian Tahir,; Arba’iyah Mohd Noor,; Mohd Firdaus Abdullah,; Suffian Mansor, (Wacana Seni Journal of Arts Discourse, 2021)
Unlike in the West, the emergence of visual printing and printing press in Malaya was comparatively lagged behind. Publication and printing reached the Malayan shore through the Straits Settlements after the first publication was brought in and introduced by A. B. Bone in 1806. Since then, various visual reports regarding Malaya made their way into the well-known newspapers in Britain, The Illustrated London News (ILN) and The Graphic. Social activities in Malaya became part of the main visual report in these newspapers. Nonetheless, it was found that these newspapers were not objective in reporting the news on social activities in Malaya. In lieu of this, the current research attempted to find out the extent of the action of ILN and The Graphic in manipulating visual news report about the social activities in Malaya in the 19th century. In addition, this research also aimed to find out how far the ideas and thoughts of both newspapers in describing the news reports related to social activities in Malaya in the 19th century. This research focuses on the 19th century, within the specified period, of which the two respective presses released many visual news reports regarding social activities in Malaya. The qualitative method and visual approach were chosen as the research itself was conducted in London, especially at the National Art Library, situated in the Victoria and Albert Museum. In Malaysia, materials and resources were obtained from the Malaysian National Archive, National Museum, National Library, and libraries at higher learning institutions.